Pengaruh pelatihan kuliner bagi juru masak terhadap mutu makanan pasien di RSUD Dr. Wahidin Sudirohusodo Makassar - Siti Fatimah; Tjahjono Kuncoro; Toto Castro (Jurnal Gizi Klinik Indonesia, 2007)
Background: The main purpose of hospital nutrition service activity is providing qualified food to patient. So far, the efforts to improve food quality in hospital have not been done integrated. Hospital still faces basic problems such as lack of cooks in either quantity or quality. Hospital needs, professional cooks who are able to serve food correctly based on standard, and providing a culinary training for the cooks is needed to improve food quality.Objective: To find out the effect of culinary training for the cook to patient’s food quality.Method: This study was a quasi-experimental with time series design. The subject of study was 30 cooks at Dr. Wahidin Sudirohusodo Hospital Makassar. Data were collected through observation and assessment using questionnaires and check-list. T-test and anova analyses were used to analyze the data on knowledge, attitude, skill of food preparation and food quality.Result: This study showed that there were improvements on scales of knowledge 8.64±2.70 (p<0.05), attitude 20.34±6.32 (p<0.05) and skill 7.89±1.64 (p<0.05) after the training. There were also improvements on food performances (color, texture, size of portion, appearance, and serving) and taste (temperature, flavor, tenderness, maturity, odor).Conclusion: There were improvements of cook’s knowledge, attitude, skill and food quality of patient after culinary training.